De intenciones y logros : fortalecimento estatal y limitaciones del nacionalismo español en el siglo xix - Isidro Sepúlveda Muñoz (Amnis)
As in the rest of Western Europe, the building of the liberal State in Spain in the 19th century ran hand in hand with Spanish nationalism, including some its peculiarities, such as the lack of synergy between the two processes. This paper analyzes some of the reasons why the building of the nation was not as successful as that of the building of the State. These include the multiplication of alternatives national models the difficulties of the public Treasury and the lack of territorial integration. Against the “weakness” theory of Spanish nationalism, the author suggests “limitations” and establishes parallelisms with national models from other European States as evidence that the Spanish case was no exception.